ANALYSIS OF EFFECT OF ORGANIZATIONAL CULTURE, WORK DISCIPLINE AND COMMITMENT ORGANIZATION, THE PERFORMANCE OF HEALTH SALIDO PARAMEDICS PAINAN - Yulihardi, Yulihardi (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
The problem is analyzed in this study is